A mixed-method approach to assessing intercultural communication needs: The case of public service interpreting in asylum contexts - Kozobolis, Stavros (International Journal of Language, Translation and Intercultural Communication, 2025)
This article focuses on examining the research methods used to evaluate intercultural communication needs in two research projects conducted between 2022 and 2024. The first, the Erasmus+ project titled “ReTrans Project: Working with Interpreters in Refugee Transit Zones: Capacity building and awareness-raising for higher education contexts”, in which DFLTI[1] participated as a partner, focused on developing digital training materials to raise awareness of interpreting in humanitarian and transborder migration contexts. The second, “Activities Arising from the Partnership Agreement with the Department of Foreign Languages, Translation and Interpreting of Ionian University”, was part of the Project “Enhancing and building-up national capacity of migration and asylum strategic planning” (Pre-defined project 3), funded by the EEA Financial Mechanism 2014-2021, and aimed to design a robust accreditation system for public service interpreters in Greece. This article summarizes and evaluates the methodologies employed in both projects. Although similar, each project approached the collection of data and its analysis from different perspectives. To this end, the main aim of the article is to reach safe conclusions on best practices for research related to public service interpreting. [1] Department of Foreign Languages, Translation and Interpreting, Ionian University, Greece.